2022
DOI: 10.1101/2022.08.17.504306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-PF4 (heparin-independent)/PF4 complex induces allosteric activation of integrins αIIbβ3 and αvβ3, a potential mechanism of vaccine-induced thrombotic thrombocytopenia (VITT) and autoimmune diseases

Abstract: The classical immune-mediated heparin-induced thrombocytopenia (HIT) is induced by autoantibody against platelet-factor 4 (PF4)/heparin complex. Vaccine-induced thrombotic thrombocytopenia (VITT) and autoimmune HIT (aHIT) are induced by anti-PF4 in a heparin-independent manner. Activation of platelet integrin αIIbβ3 is a key event that leads to αIIbβ3 binding to fibrinogen and platelet aggregation, but is not involved in current models of HIT or VITT. Anti-PF4 (heparin-independent) is also detected in autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies showed that several integrin ligands that bind to site 2 and activates integrins bound to peptides from site 2 (of β1 and β3) (Fujita et al 2014, Fujita et al 2015, Fujita et al 2018, Takada et al 2021, Takada et al 2022, Yoko K Takada 2022). We found that cyclic peptides derived from site 2 of β3 bound to FGF2 at higher levels than control scrambled β3 peptide, indicating that FGF2 is required to bind to site 2 to activate αvβ3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that several integrin ligands that bind to site 2 and activates integrins bound to peptides from site 2 (of β1 and β3) (Fujita et al 2014, Fujita et al 2015, Fujita et al 2018, Takada et al 2021, Takada et al 2022, Yoko K Takada 2022). We found that cyclic peptides derived from site 2 of β3 bound to FGF2 at higher levels than control scrambled β3 peptide, indicating that FGF2 is required to bind to site 2 to activate αvβ3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2d and 2e), which is consistent with the idea that FGF2 activates αIIbβ3 independent of inside-out signaling. Previous studies showed that several integrin ligands that bind to site 2 and activates integrins bound to peptides from site 2 (of β1 and β3) (Fujita et al 2014, Fujita et al 2015, Fujita et al 2018, Takada et al 2021, Takada et al 2022, Yoko K Takada 2022). We found that cyclic peptides derived from site 2 of β3 bound to FGF2 at higher levels than control scrambled β3 peptide, indicating that FGF2 is required to bind to site 2 to activate αIIbβ3 (paper submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Also, CD40L bound to site 2 of αIIbβ3 and allosterically activated αIIbβ3 without inside-out signaling. Two HIMG1 mutants, K143T and G144E, on the surface of trimeric CD40L suppressed CD40L-induced αIIbβ3 activation [ 50 ]. These findings suggest that CD40L binds to αIIbβ3 in a manner different from that of αvβ3 and α5β1 and induces αIIbβ3 activation.…”
Section: Cd40l Binds To Site 1 and Allosterically Activates Platelet ...mentioning
confidence: 99%
“…We showed that PF4 binds to soluble integrin αIIbβ3 in cell-free conditions but did not activate this integrin at physiological PF4 concentrations (<1 μg/mL). Notably, an anti-PF4 (RTO)/PF4 complex potently activated soluble αIIbβ3 in a heparin-independent manner [ 50 ]. We propose that anti-PF4 changed the conformation of PF4 and strongly activates αIIbβ3 by binding to site 2 and results in the strong aggregation of platelets.…”
Section: Pf4 Is An Inhibitory Chemokine: Anti-pf4 Changes the Phenoty...mentioning
confidence: 99%
See 1 more Smart Citation